Volumetric study of brain MRI in a cohort of patients with neurotransmitter disorders - Alfonsi, Chiara; Stephan-Otto, Christian; Cortès-Saladelafont, Elisenda; Palacios, Natalia Juliá; Podzamczer-Valls, Inés; Cruz, Nuria Gutiérrez; Jiménez, María Rosario Domingo; Micó, Salvador Ibáñez; Vila, Miguel Tomás; Jeltsch, Kathrin; Kuseyri Hübschmann, Oya; Opladen, Thomas; et al. (Neuroradiology, 2022)
Inborn errors of neurotransmitters are rare monogenic diseases. In general, conventional neuroimaging is not useful for diagnosis. Nevertheless, advanced neuroimaging techniques could provide novel diagnosis and prognosis biomarkers. We aim to describe cerebral volumetric findings in a group of Spanish patients with neurotransmitter disorders.